2021
DOI: 10.1002/cjoc.202100149
|View full text |Cite
|
Sign up to set email alerts
|

Facile Access to Uranium and Thorium Phosphaethynolate Complexes Supported by Tren: Experimental and Theoretical Study

Abstract: Uranium | Thorium | Tripodal ligand |Computational chemistry | Electronic structureThe issue of covalence of actinide complexes remains controversial to date. The introduction of 2-phosphaethynolate anion into actinide complexes is expected to investigate the reaction mode and the bonding property. Herein, we describe the functionalization of An(Tren TIPS )Cl (1: An = U; 2: An = Th) precursors with NaOCP(dioxane) 2.5 through salt-elimination method leading to the formation of the corresponding uranium and thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 84 publications
0
9
0
1
Order By: Relevance
“…The actinide computational chemistry can provide reliable results for the more complicated actinide complexes using the state-of-the-art computational methods thanks to its rapid development. 29–34 We optimized the structures of the four ligands, the coordination structures and the bonding nature between Am( iii )/Eu( iii ) and ligands as well as explored their Am( iii )/Eu( iii ) separation performance at the level of theory. This work provides useful information on the selectivity for An( iii )/Ln( iii ) separation of the N-heterocyclic ligands based on the preorganization strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The actinide computational chemistry can provide reliable results for the more complicated actinide complexes using the state-of-the-art computational methods thanks to its rapid development. 29–34 We optimized the structures of the four ligands, the coordination structures and the bonding nature between Am( iii )/Eu( iii ) and ligands as well as explored their Am( iii )/Eu( iii ) separation performance at the level of theory. This work provides useful information on the selectivity for An( iii )/Ln( iii ) separation of the N-heterocyclic ligands based on the preorganization strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a series of new ligands with N and O coordination sites were designed and used in the development of actinide organometallic chemistry. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] For instance, since the first example of an actinide complex supported by a triamidoamine ([(RNCH 2 CH 2 ) 3 N] 3− ) ligand (Tren) was reported by Scott and co-workers in 1994, 19 actinide organometallic chemistry with Tren ligands has flourished. 18,[20][21][22][23][24][25][26] With these trianionic ligands, a series of trivalent uranium complexes were isolated.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18] For instance, since the first example of an actinide complex supported by a triamidoamine ([(RNCH 2 CH 2 ) 3 N] 3− ) ligand (Tren) was reported by Scott and co-workers in 1994, 19 actinide organometallic chemistry with Tren ligands has flourished. 18,[20][21][22][23][24][25][26] With these trianionic ligands, a series of trivalent uranium complexes were isolated. 24,25,27,28 In 2019, we found that a novel phosphine-substituted Tren ligand (L1, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The tripodal ligand as a pocket scaffold plays a key role in immobilizing the metal ion because of its multidentate coordination, such as the typical triamidoamine (Tren) ligand. The uranium complexes with an ancillary tripodal ligand are the most versatile in uranium–ligand multiple bonds, uranium–metal bonds, small molecule activation, etc . Metal–metal (M–M) bonds represent an important branch of Werner’s classical coordination theory, , which is also an interesting organometallic chemistry research field.…”
Section: Introductionmentioning
confidence: 99%